Da sobrecarga do poder judiciário à efetividade do acesso à justiça por meio dos Mecanismos Alternativos de Solução de Conflitos (MASCS - Silva, Nathallye de Souza da; Lago, Andréa Carla de Moraes Pereira; Moreno, Thiago Leandro (Revista Terra & Cultura: Cadernos de Ensino e Pesquisa; Vol 40 No 77 (2024): Publicação Contínua, 2023)
The aim of this research is to verify the existence or (in)existence of overload in the Brazilian Judiciary, as well as whether alternative dispute resolution mechanisms (ADRMs), such as conciliation and mediation, can be considered appropriate mechanisms for resolving disputes and, consequently, for decongesting the judicial system. To this end, the methodology adopted will be the deductive, historical and comparative method, based on national and foreign bibliographical research. In addition, it is hoped to demonstrate at the end of this research that alternative dispute resolution mechanisms (ADRMs) are not only suitable, but also effective and speedy instruments for resolving conflicts, especially those of a family nature, because through these mechanisms, impartial third parties with appropriate training facilitate communication between the conflicting parties, and provide an opportunity for participatory and effective dialogue, thereby enabling the construction of a satisfactory solution for the parties and the peaceful resolution of conflicts.